The Effect of Maggot Flour (Hermetia illucens) Supplementation on Protein Consumption, Energy Consumption, and Protein Efficiency Ratio in Balenggek Crowing Chickens - Kurnianto, A; Akbar, syahro ali; Sari, Rica Mega (Department of Agriculture, 2024)
This study aimed to determine the effect of maggot flour inclusion in rations on protein consumption, energy consumption, and the protein efficiency ratio of Balenggek Crowing Chickens. The research utilized an experimental method with a Completely Randomized Design comprising 4 treatments and 4 replications. The treatments were as follows: P0 (0% maggot flour), P1 (3% maggot flour), P2 (6% maggot flour), and P3 (9% maggot flour). The results showed that protein consumption ranged from 8.33 to 8.95 g/head/week, energy consumption ranged from 1391.9 to 1446.7 kcal/head/week, and the protein efficiency ratio ranged from 4.23% to 4.53%. It can be concluded that maggot flour supplementation up to a level of 9% had a significant effect (p < 0.05) on protein consumption but did not significantly affect (p > 0.05) energy consumption or the protein efficiency ratio of Balenggek Crowing Chickens.